OPTIMALISASI POJOK BACA SEBAGAI IMPLEMENTASI GERAKAN LITERASI MASYARAKAT DI DESA PLODONGAN, KECAMATAN SUKOHARJO, KABUPATEN WONOSOBO - HIdayah, Atinia; Hidayah, Nurul (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2022)
Literation is one of the things that is intensively echoed by the government. This reading culture is a prerequisite as well as a symbol of the progress of a nation. The progress of a nation is largely determined by the extent of people awareness to increase their knowledge. Apart from formal education, increasing public knowledge can also be done through increasing interest in reading and a good literacy culture. The existence of a library in village will greatly help this movement. During the implementation of PHP2D in Plodongan Village, Sukoharjo District, Wonosobo Regency, team already provided a CafÃ© Library that integrate cafÃ© and library concept. Through the Village Empowerment Development Program (P3D) further activities were carried out in the form of optimizing the village reading corner which was carried out by providing reading corners at three points in Plodongan Village, adding book collections, updating library administration, and various teaching activities, socialization as well as literacy habituation. This activity is expected to increase people's interest in reading so that people can access a variety of information and knowledge to improve the quality and standard of living.